'I have learned from my pain': post-traumatic growth in breast cancer patients. (March 2015) - Canavarro, Maria Cristina; da Silva, Sónia Martins
SUMMARY : In this report, we highlight the positive psychological changes that may occur in the aftermath of breast cancer, known as post-traumatic growth (PTG). Assuming Tedeschi and Calhoun's conceptualization, we present the main dimensions of PTG and the prevalence in women with breast cancer. We address the issue of the adaptative significance of PTG and summarize some of the most relevant empirical studies, based on a selective review. We also reflect on the role of therapist in fostering PTG in clinical practice.